1994
DOI: 10.1073/pnas.91.20.9431
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death and AIDS: significance of T-cell apoptosis in pathogenic and nonpathogenic primate lentiviral infections.

Abstract: We have proposed that inappropriate induction of progrmmed cell death (PCD) or apoptosis, a physiological cell-suicide process, may play a role in the pathonesis of AIDS. This model has been supported by several reports of abnormal levels of PCD in vitro in both CD4+ and CD8+ T cells from human immuno iency virus type 1 (HlV-1)-infected persons. To further assess the nce of such a process In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
167
2
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(187 citation statements)
references
References 35 publications
15
167
2
2
Order By: Relevance
“…1,2,[8][9][10] The third proposed mechanism is excessive, ongoing immune activation caused by a high, persistent viral antigen load and leading to the activation-induced death of various uninfected immune cells, including CD4 þ T cells. 1,2,4,8,9 Evidence for the involvement of indirect mechanisms of CD4 þ T-cell killing has been provided by the identification in vivo [11][12][13][14][15][16] and ex vivo [17][18][19] of increased number of dying, uninfected immune cells, including CD4 þ T cells, both in HIV1-infected persons and in non-human primate models of pathogenic simian immunodeficiency virus (SIV) infection, that are closely related to HIV. An important question is whether HIV1 may only cause death in activated, cycling CD4 þ T cells, or also in unstimulated noncycling CD4 þ T cells, which represent at any given time point the vast majority of the CD4 þ T cells in HIV1-infected persons.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[8][9][10] The third proposed mechanism is excessive, ongoing immune activation caused by a high, persistent viral antigen load and leading to the activation-induced death of various uninfected immune cells, including CD4 þ T cells. 1,2,4,8,9 Evidence for the involvement of indirect mechanisms of CD4 þ T-cell killing has been provided by the identification in vivo [11][12][13][14][15][16] and ex vivo [17][18][19] of increased number of dying, uninfected immune cells, including CD4 þ T cells, both in HIV1-infected persons and in non-human primate models of pathogenic simian immunodeficiency virus (SIV) infection, that are closely related to HIV. An important question is whether HIV1 may only cause death in activated, cycling CD4 þ T cells, or also in unstimulated noncycling CD4 þ T cells, which represent at any given time point the vast majority of the CD4 þ T cells in HIV1-infected persons.…”
Section: Introductionmentioning
confidence: 99%
“…The activation-induced cell death mechanism that explains the proliferative defects observed in vitro might also account for the progressive in vivo deletion of CD4 T cells. Indeed, studies performed on different models of primates have shown that induction of cell death in CD4 T cells was detected only when T cells were isolated from animals infected with a type of retrovirus that induces an AIDS-like disease [8]. This correlation prompted us to analyse further the mechanism of HIV-induced activation cell death to determine the specificity and rate of induction of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies performed on various primate models that allow one to discriminate between biological features associated with pathogenic or non-pathogenic chronic lentiviral infections have shown that activation-induced cell death (AICD) of CD4 T cells was only observed in the model leading to AIDS [8]. In contrast, enhanced spontaneous cell death that affects mainly CD8 T cells was observed in both pathogenic and non-pathogenic models of chronic lentiviral infections [8].…”
Section: Introductionmentioning
confidence: 99%
“…Au cours de l'infection par le VIH, les lymphocytes T CD8 sont activés en périphérie, mais cependant leur état de maturation ne leur permet pas d'acquérir une activité importante vis-à-vis du VIH-1 [5]. L'une des hypothèses est que, au cours de la différenciation lymphocytaire, les lymphocytes T sont anormalement sensibles à un processus apoptotique, conduisant de ce fait à un profil de différenciation abortif, expliquant cet état d'immaturité [6][7][8]. L'apoptose est un mécanisme physiologique de suicide cellulaire, essentiel au cours du développement et au contrôle de l'homéostasie des tissus adultes.…”
Section: Inefficacité Du Contrôle Du Virus Par Les Lymphocytes T Cd8unclassified